The Lyn/RUVBL1 Complex Promotes Colorectal Cancer Liver Metastasis by Regulating Arachidonic Acid Metabolism Through Chromatin Remodeling - Zhenyu Zhang; Yina Gao; Yuanyuan Qian; Bowen Wei; Kexin Jiang; Zhiwei Sun; Feifan Zhang; Mingming Yang; Salem Baldi; Xiaoqi Yu; Yunfei Zuo; Shuangyi Ren (Advanced Science)
Abstract Liver metastasis is a common cause of death in colorectal cancer (CRC) patients, but epigenetic remodeling and metabolic reprogramming for CRC liver metastasis remain unclear. The study revealed that the Lyn/RUVBL1 complex is highly expressed in CRC and is closely correlated with liver metastasis. On the one hand, ATAC‐seq and HiCut suggested that Lyn/RUVBL1 regulates the expression of TRIB3 through the POL II‐mediated chromatin conformation of TRIB3 and thus the expression of β‐catenin. This promotes the proliferation and migration of CRC through β‐catenin‐mediated upregulation of MMP9 and VEGF. On the other hand, metabolomics revealed that Lyn/RUVBL1 regulates the expression of PGE2 through the enzyme COX2, thereby promoting arachidonic acid (AA) metabolism. CUT‐Tag showed that Lyn/RUVBL1 silencing reduces the H3K27ac level in the COX2 promoter. Then, it is found that COX2 is regulated by the transcription factor FOXA1. Lyn/RUVBL1 modulates AA metabolism by regulating the chromatin accessibility of FOXA1. AA metabolism promotes the metastasis of CRC by affecting β‐catenin nuclear translocation and upregulating MMP9 and VEGF. These findings suggest that the Lyn/RUVBL1 complex mediates epigenetic remodeling to regulate the metabolic reprogramming of AA, highlighting its role in promoting the metastasis of CRC.